Yellow dye laser thermotherapy of choroidal neovascularisation in age related macular degeneration. Issue 6 (1st June 2001) - Beintema, Margo R; Oosterhuis, Jendo A; Hendrikse, Fred
Abstract : AIM: A pilot study of the feasibility of using dye laser thermotherapy (LTT) at a subcoagulation temperature to occlude newly formed vessels in patients with age related macular degeneration (AMD). METHODS: Choroidal neovascularisation (CNV) in 24 eyes with exudative AMD was treated with a continuous wave yellow laser at 578 nm. Parameters were an exposure time of 2 or 5 seconds, a spot size of 750 or 1000 μm, and a laser power of 100–200 mW. The clinical end point was a greyish discoloration at the treatment site. The effect of thermotherapy was documented by ophthalmoscopic and fluorescein angiographic examination. The follow up after LTT was 4–16 months, mean 5 months. RESULTS: LTT resulted in total occlusion of newly formed vessels in 15 eyes (62.5%). Neovascular outgrowth within 6 weeks and recurrences 2–4 months after LTT were observed, each in three eyes. In six of the nine eyes with occlusion of CNV without recurrence the choriocapillaris remained perfused; in two eyes only the large choroidal vessels remained perfused. In six eyes pigmentary changes were the only ophthalmoscopic and fluorescein angiographic signs of treatment. The effect of LTT is rather unpredictable. CONCLUSION: CNV in AMD can effectively be treated by yellow dye laser thermotherapy with preservation of choroidal perfusion. The technique requires dosimetric adaptation.